Hubungan Profitabilitas Pada Pengungkapan Corporate Social Responsibility dengan Kepemilikan Institusional Sebagai Pemoderasi - Alerick Sumanta; Ni Made Dwi Ratnadi (Pusat Riset dan Inovasi Nasional, 2026)
Corporate Social Responsibility (CSR) has evolved into a significant endeavor and has garnered heightened scrutiny from stakeholders regarding its transparency The purpose of this research is to examine mining businesses traded on the Indonesia Stock Exchange between 2021 and 2023 in order to determine whether there is a relationship between CSR disclosure and profitability and whether institutional ownership moderates this relationship. With the help of purposive sampling, the study used 98 observation samples. Moderation regression analysis was used to analyze the relationship between variables . Profitability and CSR disclosure were shown to be positively correlated, according to the analysis. Institutional ownership does not influence the relationship between profitability and CSR disclosure. This research offers theoretical implications concerning stakeholder theory, indicating that an increase in a company's net profit enhances its capacity to implement and disclose CSR programs more effectively, thereby fostering positive relationships and addressing stakeholder interests. This research has practical implications, suggesting that investors may utilize it as a factor in executing transactions inside the capital market.